2007
DOI: 10.1016/j.arth.2006.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Wear in a Metal-On-Ceramic Total Hip Arthroplasty

Abstract: A 51-year-old woman came to our clinic 6 months after a right total hip arthroplasty. She had noticed a slowly growing mass in the proximal thigh and referred progressive pain in the right groin. Plain radiography revealed premature acetabular cup aseptic loosening, and in the computed tomography study, a 14-cm-diameter mass was observed. Revision surgery was performed, showing a metal-on-ceramic bearing surface. The histologic analysis of surrounding tissues was reported as massive metallosis. Although occasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 12 publications
2
31
0
Order By: Relevance
“…He also suggested, approved, and prohibited couplings (based on tribological reasons) to avoid dangerous head/socket combinations (Willmann, 1998). More recently Valenti et al (2007) observed massive metallosis in an implanted stainless steel femoral head against an alumina ceramic acetabular cup after 6 weeks. Williams et al (2007) and Williams et al (2008), on the other hand, observed consistent reduced ion levels in patients, who had received COM implants.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…He also suggested, approved, and prohibited couplings (based on tribological reasons) to avoid dangerous head/socket combinations (Willmann, 1998). More recently Valenti et al (2007) observed massive metallosis in an implanted stainless steel femoral head against an alumina ceramic acetabular cup after 6 weeks. Williams et al (2007) and Williams et al (2008), on the other hand, observed consistent reduced ion levels in patients, who had received COM implants.…”
Section: Discussionmentioning
confidence: 97%
“…Random assembly is, sometimes, a used practice in surgical theatre mainly in case of revision interventions (Morlock et al, 2001;Stiehl and Mahfouz, 2007;Valenti et al, 2007). The weight loss over a standard wear simulation was assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, although CoM bearings are used clinically there is little knowledge about their in-vivo performance [14]. Some case reports have shown tremendous wear of CoM [15,16], but in those cases the technical design differed from that of modern CoM bearings. Keeping this in mind, simulator studies may be an important tool for acquiring knowledge of possible CoM-related risks.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ceramic-on-metal (CoM) combinations have been tested in vitro [17][18][19][20][21][22][23][24][25][26][27][28], with a limited number being implanted in vivo [29][30][31]. Advantages of CoM over metal-on-metal (MoM) and CoC prostheses included a reduced volume of metal wear particles [26,31] and a reduced tendency for fracture of the ceramic component due to the softer metallic cup.…”
Section: Introductionmentioning
confidence: 99%